One-dimensional Sb2Se3 enabling ultra-flexible solar cells and mini-modules for IoT applications. (August 2021) - Li, Kanghua; Li, Fu; Chen, Chao; Jiang, Pengfei; Lu, Shuaicheng; Wang, Siyu; Lu, Yue; Tu, Guoli; Guo, Jiaojiao; Shui, Langquan; Liu, Ze; Song, Boxiang; et al.
Abstract: Power supply equipment, employed in the Internet of Things (IoT) for instance, calls for efficient harvesting of solar energy from the environment sustainably. Sb2 Se3 enjoys the advantages of unique one-dimensional crystal structure and low-temperature film growth, enabling the fabrication of flexible and lightweight solar cells. Therefore, Sb2 Se3 solar cells are expected to have intrinsic advantages in powering IoT sensors. Herein, the device configuration and film fabrication of flexible Sb2 Se3 solar cell was optimized and an efficiency up to 6.13% and power-per-weight of 2.04 W g -1 were obtained, both of which are the highest records for flexible Sb2 Se3 solar cells. Benefitting from the intrinsically high flexibility of Sb2 Se3 and the thin flexible substrate, our device retained 96% of its initial performance after 1000-times bending at the extremely small curvature radius of 0.5 mm. Furthermore, the first Sb2 Se3 mini-module (25 cm 2 area) was constructed and its application in powering a blue LED under all weather conditions and a flower monitor (IoT sensors) was demonstrated. This work opens an avenue toward flexible Sb2 Se3 solar cells and points out its future research direction. Graphical Abstract: Solar cells, with high energy density and reliability, can serve as the power source for the sensors of the Internet of Things (IoT) sensor. Combining the intrinsically high flexibility of Sb2 Se3 and careful analysis of stain distribution, lightweight and ultra-flexible Sb2 Se3 solar cells and mini-modules were obtained and successfully applied to IoT sensors as energy supply. ga1 Highlights: The analysis of material mechanics and stain distribution guide the design of ultra-flexible Sb2 Se3 solar cells. The flexible Sb2 Se3 solar cells exhibit high efficiency of 6.13%, high power-per-weight of 2.04 W g -1 . The flexible Sb2 Se3 solar cells keep 96% of the initial PCE after 1000-times bending at a curvature radius of 0.5 mm. The large-area (~ 25 cm 2 ) flexible Sb2 Se3 solar mini-modules are successfully applied for power supply of IoT sensors.